Legal Responsibility of Coal Mining Company PT. International Prima Coal for Worker Welfare and Safety - Suryaningsi, Suryaningsi; Herliah, Endang; Syarif, Muhammad; Rosmini , Rosmini; Yuliangrum , Aullia Vivi; Bahzar, Moh (Journal of Ecohumanism, 2024)
Pancasila provides the direction and foundation for the formation of laws, policies and actions of the Indonesian government. This principle emphasizes the need to overcome social, economic, and political inequalities and provide equal opportunities for all Indonesians to prosper. This reflects a commitment to creating a just society. The method used in this study is qualitative using a qualitative descriptive approach, the data collection techniques used are interviews, observation, and documentation. From the results of the first study, mining business actors regarding the protection of women’s labor rights still have women’s labor rights that have not been fully fulfilled so that in this case it is not in accordance with Law No. 6 of 2023. Unfulfilled rights are menstrual leave and miscarriage leave. Furthermore, regarding the equality of women workers, it is proven by the existence of female workers who serve as Managers and there is no difference in the nominal salary. While the implementation of Corporate Social Responsibility funds of PT. International Prima Coal is good enough according to government regulations because it meets all aspects of the East Kalimantan Blue Print. Implementation of Corporate Social Responsibility funds of PT. International Prima Coal is also in accordance with the perspective of Islamic Economics.